Single breath carbon monoxide transfer factor in different forms of chronic airflow obstruction in a general population sample. - Knudson, R J (1990)
The single breath transfer factor for carbon monoxide (TLCO), TLCO/alveolar volume (VA), and standard spirometric indices were measured in a survey of the randomly selected population sample of 1174 subjects enrolled in the Tucson epidemiological study of airways obstructive disease. Subjects were subdivided according to whether the FEV1/FVC ratio was under 65%, 65-75%, or over 75%. The influence of smoking on TLCO was accounted for by expressing TLCO as a percentage of the expected value-that is, of the value expected from the reported cigarette consumption. The 63 subjects who gave a history of physician confirmed asthma in reply to a questionnaire tended to have high values for TLCO, even when FEV1/FVC was reduced. In the absence of a given diagnosis of asthma, however, TLCO and TLCO/VA were reduced when the FEV1/FVC ratio was reduced, whether or not a clinical diagnosis of emphysema had been reported. This suggests that these subjects may have undiagnosed emphysema. This cross sectional analysis of our survey data suggests that subjects in our sample with spirometric evidence of chronic airflow obstruction have different forms of disease, characterised by different physiological features, in addition to the different risk factors and clinical courses reported earlier.